The Palgrave International Handbook on Adult and Lifelong Education and Learning (Palgrave Macmillan UK, 2018)
This Handbook provides a wide-ranging frame of reference for researching adult and lifelong education and learning. With contributions from scores of established and newer scholars from six continents, the volume covers a diverse range of geopolitical and social territories across the world. Drawing on the multiple heritages that underpin research on education and learning in adulthood, this Handbook addresses the inner tensions between adult education, adult learning, lifelong education, and lifelong learning, by using current research and theorizations from disciplinary backgrounds, including philosophy, psychology, biology and neuroscience, anthropology, sociology, history, political science, and economics. It provides an explicit discussion of the differences and tensions between adult and lifelong education and learning, and locates these in different policy and historical contexts, theories and practices. It explores a variety of discipline-based theoretical perspectives, and highlights how these have influenced, and been influenced by, research in the education and learning of adults. The Handbook also explores the inevitable frictions and dilemmas these present, and carefully examines the role of the international dimension in researching education and learning in formal, non-formal and informal contexts, beyond traditional schooling. This state-of-the-art, comprehensive Handbook is the first of its kind to explore adult education, lifelong education and lifelong learning fully as distinct activities on an international scale. It will be an indispensable reference resource for students of education at undergraduate and postgraduate levels, and for academic researchers, professionals and policy-makers concerned with adult and community education, further and vocational education, or work-based training and human resource development. .